Blessing in disguise for Siti Hanisah, a recipient of UMP’s MyGift programme - UMP, PNC (2019)
It was to be one of the happiest days of her life and a day that should be celebrated with the beloved ones but Siti Hanisah Syed Hassan came alone to register as a new student in Universiti Malaysia Pahang (UMP) on September 2, 2019.